2018
DOI: 10.3390/ma11020229
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Octacalcium Phosphate Collagen Composite for Titanium Dental Implants in Dogs

Abstract: Background: Previous studies showed that octacalcium (OCP) collagen composite (OCP/Col) can be used to repair human jaw bone defects without any associated abnormalities. The present study investigated whether OCP/Col could be applied to dental implant treatment using a dog tooth extraction socket model. Methods: The premolars of dogs were extracted; each extraction socket was extended, and titanium dental implants were placed in each socket. OCP/Col was inserted in the space around a titanium dental implant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…osseointegration to autologous bone graft in a study of the mandible in a canine model. 25 On the other hand, the ISQ value showed no significant difference between the two time points under the simultaneous approach, but was high enough at the initial operation, meaning that implant stability was obtained by the remaining host bone.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…osseointegration to autologous bone graft in a study of the mandible in a canine model. 25 On the other hand, the ISQ value showed no significant difference between the two time points under the simultaneous approach, but was high enough at the initial operation, meaning that implant stability was obtained by the remaining host bone.…”
Section: Discussionmentioning
confidence: 91%
“…The value increased from 59.5 at implant placement to 72.0, indicating the completion of osseointegration at the second operation, 6 months after the initial operation, using the staged approach [Figure (c)]. OCP/Col graft around the implants is also reported achieving comparable osseointegration to autologous bone graft in a study of the mandible in a canine model . On the other hand, the ISQ value showed no significant difference between the two time points under the simultaneous approach, but was high enough at the initial operation, meaning that implant stability was obtained by the remaining host bone.…”
Section: Discussionmentioning
confidence: 99%
“…The results in these studies indicated the following: OCP/Col can be converted to normal bone tissue in critical-sized bone defects in the calvarium without remaining as a foreign body, 25,26 OCP/Col can retain the shape of the alveolar bone after tooth extraction without bone resorption, 27 the gap in the alveolar bone cleft can be filled with newly formed bone after OCP/Col implantation, 28,29 a permanent tooth can normally erupt in the newly formed bone after OCP/Col implantation in the extraction socket of deciduous teeth, 30 OCP/Col can facilitate bone augmentation in the mandibular alveolar bone defect with titanium mesh, 31 and newly formed bone after OCP/Col implantation can have the same osseointegration for titanium dental implant surfaces as autologous bone. 32 The first clinical application of OCP/Col has been conducted in the bone defect caused by tooth extraction or cystectomy in 10 patients in a clinical study of bone regenerative therapy by OCP/Col composites (registered with JPRN-UMIN000004655 in the University Hospital Medical Information Network in Japan (UMIN) and International Clinical Trials Registry Platform Search Portal of the World Health Organization, from 2011 to 2013 at Tohoku University Hospital), 33,34 as a preclinical trial. The first objective of this study was to investigate the safety of OCP/ Col in clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic materials like hydroxyapatite (HAp) have been mostly used in bone regeneration approaches, due to its exceptional mechanical stiffness and osteoinductivity [ 74 , 76 ]. Metallic scaffolds based on tantalum or titanium are also used as subchondral bone substitutes alone or in combination with other biomaterials in composite scaffolds [ 95 , 96 , 97 ]. Their lack of degradation and the possibility of releasing corrosion products are concerns to be considered [ 74 ].…”
Section: Scaffolds For Osteochondral Repairmentioning
confidence: 99%